Improving adolescent health literacy through school-based health literacy intervention: a mixed-method study protocol - Shanti Prasad Khanal; Chitra Bahadur Budhathoki; Orkan Okan (BMC Public Health, 2023)
Abstract Background Health-promoting actions might benefit from adolescent health literacy (AHL), however, there is scant research on it in Nepal. This study identifies adolescent students’ health literacy (HL) needs and trials an intervention to improve their HL and intention to take health-promoting actions. Methods This study employs a pre-and post-test mixed-method intervention involving three phases. First, we will conduct a formative and summative evaluation to identify participants’ HL needs and design an intervention using quantitative and qualitative methods. Second, the intervention will be administered to the intervention group. Finally, formative and summative post-tests will be conducted to assess the effectiveness of the intervention. We will select four community schools from Birendranagar municipality based on random sampling. In quantitative research, data will be collected from adolescents selected through a census with standardized scales such as the HLS-Child-Q15, self-efficacy, social support, and health-promoting actions. A framework analysis was conducted to analyze qualitative data collected from focus group discussions with purposively chosen adolescents and key informant interviews with Health and Physical Education teachers and school nurses. The difference in difference approach will be used to analyze the intervention’s outcome, i.e., the participants’ improved HL, and health-promoting actions. Discussion This is one of the first studies to explore HL in this group in Nepal. This study will provide the first insights into the overall level of AHL, potential AHL determinants, and the relationship between AHL and the intention to participate in health-promoting activities. The data can then be used to inform health promotion and health literacy initiatives.